Readaptation Treatment of Mal de Debarquement Syndrome With a Virtual Reality App: A Pilot Study - Yakushin, Sergei B.; Zink, Reilly; Clark, Brian C.; Liu, Chang (Frontiers in Neurology, 2020)
Mal de Debarquement Syndrome (MdDS) is comprised of constant phantom sensations of motion, which are frequently accompanied by increased sensitivity to light, inability to walk on a patterned floor, the sensation of ear fullness, head pressure, anxiety, and depression. This disabling condition generally occurs in premenopausal women within 2 days after prolonged passive motion (e.g. travel on a cruise ship, plane or in a car). It has been previously hypothesized that MdDS is the result of maladaptive changes in the polysynaptic vestibulo-ocular reflex (VOR) pathway called velocity storage. Past research indicates that full-field optokinetic stimulation is an optimal way to activate velocity storage. Unfortunately, such devices are typically bulky and not commonly available. We questioned whether virtual reality (VR) goggles with a restricted visual field could effectively simulate a laboratory environment for MdDS treatment. A stripes program for optokinetic stimulation was implemented using Google Daydream Viewer. Five female patients (42±10 years; range 26-50), who’s average MdDS symptom duration was 2 months, participated in this study. Four patients had symptoms triggered by prolonged passive motion and in one, symptoms spontaneously occurred. Symptom severity was self-scored by patients on a scale of 0-10, where 0 is no symptoms at all and 10 is the strongest symptoms that the patient could imagine. Static posturography was obtained to determine objective changes in body motion. The treatment was considered effective if the patient’s subjective score improved by at least 50%. All five patients reported immediate improvement. On two-month follow-ups, symptoms returned only in one patient. These data provide proof-of-concept for the limited visual field googles potentially having clinical utility as a substitute for full-field optokinetic stimulation in treating patients with MdDS in clinics or via telemedicine.